PERANCANGAN DATABASE SISTEM INFORMASI AKUNTANSI PENJUALAN DI UD. NIWATORI - Khalilullah, Khalilullah; Evayani, Evayani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this research is to understand of data processing and also to design database accounting information system of sales cycle of UD. Niwatori. The company is located in Kuta Malaka, Aceh Besar, which is engaged on business of livestock and eggs. Nowadays, UD. Niwatori uses manual system in running the business. This situation makes UD. Niwatori difficult in producing information in detail, especially in the sales cycle. In this study, data used is primary data in the form of interviews with parties involved in the sales cycle and secondary data in the form of documents used in the sales cycle. The result of this research is the applicable database management system of sales cycle